Climate Conversations: An Intergenerational Artistic Exploration with Family - Julia A Craven (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2025)
This cross-generational study explores perceptions of climate change through interviews and visual art from three generations: the author, their grandparents, and their aunt. Guided by questions such as “Whose responsibility is it to address climate change?” and “How has climate change affected you?,” the interviews were used to create three art pieces that explore different aspects of climate change. The first art piece, titled “Eco-Anxiety,” visually represents the author's anxiety about climate change through the detangling of hair in their hands that "pull" at relevant climate news articles in the background. The second piece, “Beauty’s in the Eye of the Beholder,” features the author's grandmother holding a flower, reflecting the older generation’s desire to hold onto an idealized view of nature. “Flowers in July,” the final piece, features the author's aunt handing a flower to their cousin, symbolizing the passing on of environmental problems to a new generation. Color (or lack thereof) in each piece represents hope and optimism for the future. This project highlights the personal nature of climate change and the intergenerational impact of environmental problems.